Penggunaan Media Edpuzzle Dalam Meningkatkan Kemampuan Membaca Al-Qur’an Siswa Di SMAN 5 Palangka Raya - Selfia, Mega; Azis, Abdul; Rizal, Setria Utama (Jayapangus Press, 2025)
Some class X students at SMAN 5 Palangka Raya face problems reading the Qur'an correctly, especially constrained by tajweed, letter makhraj, and fluency. In class X, PAI teachers have never used technology-based media. This condition requires the right way to improve students' ability to read the Qur'an with interesting and interactive learning media. This study aims to analyze students' activities in the Qur'an learning process, as well as to see the improvement of students' Qur'an reading ability at SMAN 5 Palangka Raya by using Edpuzzle media. This research uses quantitative method with pre-experimental design in the form of one group pretest-posttest design. Data collection techniques are observation, test, documentation. The results of this study show that students benefit from the use of Edpuzzle media, the acquisition of the Paired Sample T test found a real difference between the ability of students before and after treatment, with a sig. value of 0.000 <0.05. The calculated t-value is -9.118, meaning that the average is lower before treatment than after treatment. Analysis of the N-Gain of 0.3324 places the increase in results in the moderate category. The use of Edpuzzle in learning to improve the ability to read the Qur'an at the high school level is still rarely studied, so this research is expected to contribute to the utilization of Edpuzzle as a media innovation that supports Qur'an learning in schools.